PENGUKURAN IT READINESS PADA KBRI QUITO EKUADOR SEBAGAI PERWAKILAN PERTUKARAN BUDAYA MENGGUNAKAN TRI MODEL - Rahmat Yasirandi; Dita Oktaria; Muhammad Karoma Yuda (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2021)
The use of online platforms in cultural exchange is something new, so everyone has a different level of readiness. Therefore, a review is needed to determine a person's level of readiness to accept technology. In line with the existing problems, this study was made to measure the level of readiness to adopt technology. This study selects a case study of online platform technology in cultural exchange. The measurement method used in this study uses the Technology Readiness Index (TRI) model. This study used 8 official staff of the Indonesian Embassy in Quito as the sample. Research data collection is done by distributing questionnaires. After the data is collected, data analysis is carried out using the TRI value test. From the TRI test, the value is 3.49, where the value is categorized at the Medium Technology Readiness level. In the TRI model, the level of readiness is categorized as Medium Technology Readiness if the TRI value is between 2.90 to 3.51. From the results obtained, it can be concluded that the official staff of the Indonesian Embassy in Quito are ready to implement cultural exchange with an online platform, because the level of readiness is in the Medium Technology Readiness category.